CHAVE ILUSTRADA PARA OS GÊNEROS DE BORAGINACEAE senso lato NATIVOS DO BRASIL - José Iranildo Miranda de Melo; Renan da Cruz Paulino; Frank Valdomiro da Silva (Revista Caatinga, 2007)
This work was based on dried specimens, including types, field works (collects and observations) mainly in Brazilian Northeastern, as well as information obtained in the specialized literature. Eleven genera, and approximately 150 species, belonging to four subfamilies were recorded: Boraginoideae, Cordioideae, Ehretioideae and Heliotropioideae. An illustrated key to the recognition of the genera of Boraginaceae native from Brazil based on its floral and fruit features are presented.